Access and longitudinality of prison health care: Perspectives of family medicine in addressing neglected populations and diseases (Research, Society and Development, 2024)
Built on a historical process of exclusion and confinement of what is socially and legally determined as criminal behavior, the biopsychosocial nature of criminality continues to increase the number of populations that overcrowd the prison system, but in a proportion that diverges from the real needs for investment in reeducation, in the possibilities of psychosocial reintegration and the guarantee of human rights within the regime of deprivation of liberty, especially access to health. Within the gaps and weaknesses that exist in the full guarantee of health in the entire vision of physical and mental well-being, the existence of neglected diseases is a growing problem. Even though they are in the process of reduction in the general population, they are still a present reality and difficult to manage in the follow-up of neglected populations, requiring a health organization that allows the direction of studies and approaches that empower and assist in health education, prevention and promotion of these marginalized populations. Based on this scenario, family and community medicine is strategic medical training for work in neglected areas and zones. This study aims to conduct a narrative review of the literature on the issue of access and comprehensive care required in prison health, with family and community medicine responsible for coordinating care and the general understanding of the growth and identification of neglected diseases in these invisible segments of society.